Does IMF Financing Result in Moral Hazard? - Phillips, Steven; Lane, Timothy (Washington, D.C. : International Monetary Fund, 2000)
The view that the IMF's financial support gives rise to moral hazard has become increasingly prominent in policy discussions, particularly following the 1995 Mexican crisis. This paper seeks to clarify a number of conceptual issues and bring some basic empirical evidence to bear on this hypothesis. While some element of moral hazard is a logical consequence of the IMF's financial support, such moral hazard is difficult to detect in market reactions to various IMF policy announcements and there is no evidence that such moral hazard has recently been on the rise.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet